Evaluation of solid carbide end mill with wiper geometry / Nurul Ashieqin Mohd Maznihan ... [et al.] - Mohd Maznihan, Nurul Ashieqin; Mohd Shapri, Illya; Rosle, Sharifah Suraya; Rosni, Afeeq Azhan; Mohd Rodzi, Ana Syahidah; Zubair, Ahmad Faiz (2022)
In this work, we studied the difference in the surface finish using two types of end mill tools bit with wiper and no-wiper coated using the DMU 50 5-axis Computer Numerical Control (CNC) machine. One of the primary goals of the manufacturing business is to optimize the efficiency of producing high- quality, well-finished products. Our aim is to get the surface finish by 0.035 μm. This value of surface roughness is targeted by the standard of toolmaker in the industry. The workpiece will undergo roughing process first before the finishing process is performed. Simulation of both roughing and finishing processes was conducted using the Fusion 360 CAD software. The spindle speed and the feed rate during the machining process have been standardised for all lengths of the overhangs tested. The surface finish of the machining workpiece was verified using the finishing milling process. In this process, the overhang of the tool bits has been varied to 40,50, and 60 mm in lengths. The roundness test of the tool bit has also been performed before the machining process in order to make sure the result that we get in this experiment is reliable. Optical imaging and surface roughness tests were done to obtain the differences between the wiper and no-wiper finishing. The result shows a very huge differences gap between the wiper and no-wiper finishing percentage of the machining surface roughness. The wiper end mills have obtained the targeted value of the finished surface. We also found that the higher the overhang length tested, the higher the rate at which the tool bits vibrate during the machining processes. Because of its potential to enhance the production finishing result, the tool bit that includes a wiper should be utilised more frequently in industrial settings.